A Synthetic Fluorescent Mitochondria‐Targeted Sensor for Ratiometric Imaging of Calcium in Live Cells. Issue 29 (7th June 2019) - Pendin, Diana; Norante, Rosa; De Nadai, Andrea; Gherardi, Gaia; Vajente, Nicola; Basso, Emy; Kaludercic, Nina; Mammucari, Cristina; Paradisi, Cristina; Pozzan, Tullio; Mattarei, Andrea
Abstract: Ca 2+ handling by mitochondria is crucial for cell life and the direct measure of mitochondrial Ca 2+ concentration in living cells is of pivotal interest. Genetically‐encoded indicators greatly facilitated this task, however they require demanding delivery procedures. On the other hand, existing mitochondria‐targeted synthetic Ca 2+ indicators are plagued by several drawbacks, for example, non‐specific localization, leakage, toxicity. Here we report the synthesis and characterization of a new fluorescent Ca 2+ sensor, named mt‐fura‐2, obtained by coupling two triphenylphosphonium cations to the molecular backbone of the ratiometric Ca 2+ indicator fura‐2. Mt‐fura‐2 binds Ca 2+ with a dissociation constant of ≈1.5 μm in vitro. When loaded in different cell types as acetoxymethyl ester, the probe shows proper mitochondrial localization and accurately measures matrix [Ca 2+ ] variations, proving its superiority over available dyes. We describe the synthesis, characterization and application of mt‐fura‐2 to cell types where the delivery of genetically‐encoded indicators is troublesome. Abstract : Calcium monitoring : A selective mitochondria‐targeted ratiometric fluorescent chemical Ca 2+ sensor, mt‐fura‐2, is obtained by coupling two triphenylphosphonium cations to Ca 2+ probe fura‐2. When loaded in different cell types as acetoxymethyl ester, the probe shows proper mitochondrial localization and accurately measures matrix [Ca 2+ ] variations.